Writing postcolonial history - Rochona Majumdar (Bloomsbury, 2010)
Writing Postcolonial History addresses the relationship between postcolonial theory and history. It provides students with critical analyses of postcolonial histories from around the world. In addition, it discusses the benefits and shortcomings of this form of writing by situating postcolonial history amidst other modes of historical inquiry.